Examining the Religiosity of Bendar Fishermen in Central Java: A Da’wah Perspective - Saerozi, Saerozi; Setiawan, Asep Iwan; Musyafak, Najahan; Susanto, Dedy; Hakim, Lukmanul; Azizy, Dimas Fahmi (Jurnal Dakwah Risalah, 2024)
Fishermen are generally stereotyped as a marginalized group characterized by poverty, low levels of education, lack of religious observance, engagement in superstitious rituals, extravagance, alcohol abuse, and other negative behaviors. However, in reality, fishing communities are both relatively prosperous and deeply religious. This study addresses the following research questions: What are the religious connotations associated with fishermen in Bendar Village? What is the reality of their religious practices? How are their religious practices perceived through the lens of Islamic preaching (da'wah)? The research employs a qualitative descriptive approach. The findings reveal that fishermen in Bendar Village, Pati Regency, Central Java Province, actively practice Islamic traditions such as Quranic recitation, tahlil, and manaqib. Additionally, they are industrious individuals, and many within their families have attained higher education, with several holding university degrees. This phenomenon implies that the religious practices of fishermen can be understood as a culturally grounded approach to Islamic preaching (da'wah), highlighting the integration of local traditions within the broader framework of religious dissemination.